Instilling The Value of Multiculturalism Based on The Quran and The Huma Betang Philosophy - Aulia Kiftiah; Ahmadi; Ajahari (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2025)
This study aims to instill the values ​​of multiculturalism based on the Qur'an and the philosophy of Huma Betang in the context of a multicultural Indonesian society. The method used is a literature study, which involves collecting and analyzing data from various written sources, including books, articles, and scientific journals. The results of the study indicate that multiculturalism in Indonesia, which is reflected in the motto